Creative business on the example of a company operating in the insulation materials industry - Drzazga, Agnieszka (Creativity in Business Practice. Part 2, 2019)
The chapter addresses the issues of creativity and innovation in business practice on the example of a small company located in Lodz and operating on the market of insulating materials. This study is of a theoretical and empirical nature and consists of several parts. The first one is an introduction to the subject of entrepreneurship, creativity and innovativeness of enterprises. Chapter One presents the definitions of creativity and innovation and their significance for the success of modern enterprises. Chapter Two features the Lodz based enterprise operating in the insulation materials industry and presents the results of the interview conducted with the owner of the researched company in the form of a case study. The last part presents conclusions from the conducted research and a summary. The conducted survey in the form of an interview with a company operating in the field of insulation materials allowed for presentation of this company in this chapter as an example of a learning, creative and innovative organization.